(NiZBRANNOE W PQTI KNIGAH oPERY PO ROMANAM DOSTOEWSKOGO(B.s (NMONOGRAFIQs - (N`(B. (NdMITRINs ((NsANKT(B-(NpETERBURG(B.s (NlANX(B.s (NpLANETA MUZYKI(B.s, 2024)
(NdANNAQ SERIQ KNIG WKL@^AET W SEBQ SO^INENIQ DRAMATURGA `RIQ dMITRINA iZBRANNOE W PQTI KNIGAH(B.s
Keywords: (NmONOGRAFIQs